Prognostic impact of cysteine proteases cathepsin B and cathepsin L in pancreatic adenocarcinoma - Niedergethmann, Marco; Wostbrock, Birgit; Sturm, Jörg; Willeke, Frank; Post, Stefan; Hildenbrand, Ralf (Pancreas, 2004)
Objectives: The cysteine proteases cathepsin B (CTSB) and L (CTSL) have been implicated in tumor spread and metastatic formation. In pancreatic adenocarcinoma, the role of these proteases is not very well defined. To find out which cell types produce CTSB and CTSL and to evaluate the prognostic impact of these proteases, 70 specimens from curatively resected patients with pancreatic adenocarcinoma were examined by in situ hybridization and immunohisto-chemistry. Methods: Seventy patients with ductal adenocarcinoma of the pancreas were studied after R0 resection with a follow-up of at least 3 years. CTSB and CTSL expression was performed immunohisto-chemically using polyclonal anti-CTSB and CTSL antibodies. To detect cell types involved in producing CTSB and CTSL as well as the intracellular localization of specific mRNA sequences, nonisotopic in situ hybridization was performed. The correlations among CTSB and CTSL expression, clinicopathologic parameters, and clinical outcome were analyzed. Results: The immunoreactivity was 96% for CTSB and 90% for CTSL. Positive mRNA signals were obtained in the cytoplasm tumor cells, macrophages, and fibroblasts in 77% for CTSB and 81% for CTSL, respectively. Statistical analysis showed a significant correlation between CTSB/CTSL expression and tumor grading (P < 0.05) and between CTSB and lymphatic invasion (P = 0.05). Kaplan-Meier analyses revealed statistical significance for CTSB/CTSL expression with the survival after curative resection (P < 0.05). Both proteases are strong prognostic markers in multivariate analysis (P = 0.0001) beside UICC stage, nodal status, tumor size, and grading (P < 0.05). Furthermore, CTSB expression is an independent prognostic marker for cancer recurrence within 6 months after curative surgery in multivariate analysis (P = 0.0001). Conclusions: CTSB and CTSL are strong and independent prognostic markers in resectable pancreatic adenocarcinoma rather than UICC stage, TNM classification, or tumor grading. Furthermore, CTSB is a predictor for early recurrence after curative resection. These data underline the significance of tumor-associated proteolysis for cancer invasion and metastasis and may lead to defining subgroups of patients with early recurrence and poor outcome.